The quadratic with a root of a root of a quadratic

Algebra Level 1

The equation x 2 a x + 1 = 0 x^2 - ax + 1 = 0 has real solutions, the greater of which is r . r.

Now, let b b be a positive real number such that the greater solution of the equation x 2 b x + 1 = 0 x^2 - bx + 1 = 0 is r . \sqrt{r}.

If a = 79 , a = 79, then what is b ? b?


The answer is 9.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

9 solutions

Bufang Liang
Oct 9, 2018

Instead of directly using x 2 79 x + 1 = 0 x^2 - 79x + 1 = 0 , we will simply use x 2 a x + 1 = 0 x^2 - ax + 1 = 0 as a generalization (assuming a > 0 a > 0 of course), and then obtain a formula we can just plug in.

We present two solutions:

Solution 1: r 2 a r + 1 = 0 r^2-ar+1 = 0 a = r 2 + 1 r a = \frac{r^2+1}{r} r b r + 1 = 0 r-b\sqrt{r}+1 = 0 b = r + 1 r b = \frac{r+1}{\sqrt{r}} b 2 = r 2 + 2 r + 1 r b^2 = \frac{r^2+2r+1}{r} b 2 = a + 2 b^2 = a+2 b = a + 2 b = \boxed{\sqrt{a+2}}

Solution 2: ( x 2 b x + 1 ) ( x 2 + b x + 1 ) = x 4 ( b 2 2 ) x 2 + 1 = 0 (x^2-bx+1)(x^2+bx+1) = x^4 - (b^2-2)x^2 + 1 = 0 b 2 2 = a b^2 - 2 = a b = a + 2 b = \boxed{\sqrt{a+2}}

Plugging in our value of a a , we get that b = 79 + 2 = 9 b = \sqrt{79+2} = \boxed{9} .

Very nice.

Richard Desper - 2 years, 7 months ago

Wait how does solution 2 work? Why is one of them +b?

Joshua Perrett - 2 years, 7 months ago

Log in to reply

The value x is here sqrt(r). So the expression in the brackets on the left side is zero. So the whole product is zero. If you multiply with the other expression you get the equation with factor a and solution r.

Stefan Volland - 2 years, 7 months ago
Paul Thompson
Oct 22, 2018

In both equations the product of the roots is 1. So the first equation has roots r and 1 r \frac{1}{r} while the second has roots r \sqrt{r} and 1 r \frac{1}{\sqrt{r}} .

Considering sums of roots we have r + 1 r = a r + \frac{1}{r} = a and r \sqrt{r} + 1 r \frac{1}{\sqrt{r}} = b

Squaring the second of these equations yields r + 1 r + 2 = b 2 r + \frac{1}{r} + 2 = b^2 and therefore a + 2 = b 2 a + 2 = b^2

Substituting a=79 and taking the positive square root gives b = 9 b = 9

Forgot the ^2 in the first appearance of b in your third paragraph.

Richard Desper - 2 years, 7 months ago

Log in to reply

Thanks - now updated

Paul Thompson - 2 years, 7 months ago

Beautiful, simple solution!

John Pabrinkis - 2 years, 7 months ago

Good and simple solution.

Ravi Bendi - 2 years, 7 months ago

Can you please detail the part where you say that « in both equation products of the roots is 1 » ? Thanks

Thomas AMET - 2 years, 7 months ago

Log in to reply

It comes from the Viete formulas: in a polynomial equation, the product of the roots equals the coefficient of the zero-degree term divided by the coefficient of highest degree.

Giacomo Lanza - 2 years, 4 months ago
Chew-Seong Cheong
Oct 17, 2018

Given that r r is a root of x 2 a x + 1 = 0 x^2 - ax+1 = 0 , therefore, r 2 a r + 1 = 0 r^2 -ar + 1 = 0 and a = r 2 + 1 r \implies a = \dfrac {r^2+1}r . Similarly, given that r \sqrt r is a root of x 2 b x + 1 = 0 x^2 - bx+1 = 0 , then

b = r + 1 r = ( r + 1 ) 2 r = r 2 + 2 r + 1 r Note that a = r 2 + 1 r = a + 2 and a = 79 = 79 + 2 = 9 \begin{aligned} b & = \frac {r+1}{\sqrt r} \\ & = \sqrt{\frac {(r+1)^2}r} \\ & = \sqrt{\frac {r^2+2r+1}r} & \small \color{#3D99F6} \text{Note that }a = \frac {r^2+1}r \\ & = \sqrt{a+2} & \small \color{#3D99F6} \text{and }a = 79 \\ & = \sqrt{79+2} \\ & = \boxed{9} \end{aligned}

Typical Beam
Oct 23, 2018

r 2 79 r + 1 = 0 r^2-79r+1=0 ( r 2 + 2 r + 1 ) 81 r = 0 (r^2+2r+1)-81r=0 ( r + 1 ) 2 = 81 r (r+1)^2=81r Since r > 0 r>0 , taking square-root on both sides, we get r + 1 = 9 r r+1=9\sqrt{r} r 2 9 r + 1 = 0 \sqrt{r}^2-9\sqrt{r}+1=0 So b = 9 b=9

Vinod Kumar
Oct 23, 2018

Product of the roots is=1 fir both equations, the sum of the roots give relation b^2-2=79, therefore,

Answer is, b=9

Peter Macgregor
Oct 22, 2018

We will use the fact that for a monic quadratic equation the sum of the roots is given by the negative of the coefficient of x x and the product of the roots is given by the constant term. Let R and r be the bigger and smaller root of the first equation, then

R + r = 79 R r = 1 R+r=79 \\ Rr=1

The second equation with smaller root ρ \rho gives

R + ρ = b R ρ = 1 \sqrt{R} + \rho = b \\ \sqrt{R} \rho = 1

Using these pairs of equations to eliminate the smaller roots gives

79 = R + 1 R ( 1 ) b = R + 1 R 79=R+\dfrac{1}{R} \dots(1) \\ b=\sqrt{R}+ \dfrac{1}{\sqrt{R}}

Squaring this last equation gives

b 2 = R + 1 R + 2 b^2=R+ \dfrac{1}{R}+2

Then using equation (1) gives

b 2 = 79 + 2 = 81 b^2=79+2=81

And so b (we are told t is positive) is 9 \boxed{9}

Alex Jones
Oct 28, 2018

Gentle reminder that Desmos exists

Got the correct answer, but did it the brute force way.

I only wanted to comment that you may want to be more precise with your definitions. Specifically, x 2 a x + 1 = 0 x^2-ax+1=0 has real solutions only when a 2 \lvert a \rvert \geq 2 ; the argument is the same when you replace a a with b b .

Aside from that, nice problem!

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...